The origin of spring-like leg behaviour in long jump - Seyfarth,A.; Bobbert, M. F.; Blickhan, R.
In this study the origin of spring-like leg behaviour in long jump is addressed. Therefore, a forward dynamic model of the human musculoskeletal system was used to study the interaction between segment dynamics and muscle dynamics. The model consists of four rigid segments representing the upper body (head, both arms, trunk and swing leg: HATL) and the stance leg (foot, shank and thigh) and six major muscle-tendon complexes (MTCs) acting on the intersegmental hinge joints. Muscle stimulation STIM(t) was optimised for maximum jumping distance whereas each muscle was allowed to switch on only once. This allowed us to investigate the following aspects: (1) To what extend is spring-like operation supported by inherent MTC properties? (2) How is spring-like operation supported by segmental arrangement during leg loading? (3) Which effects are contributing to the passive force peak? It was found that: (1) Optimising jumping performance leads to spring-like leg behaviour. (2) Thereby, synchronous and quasi-elastic ankle and knee joint loading occurred. (3) Leg stiffness is an overall behaviour of the whole body and originates from a synchronised, quasi-elastic muscle operation reducing intermuscular and interarticular energy losses. (4) Highly activated MTCs show quasi-elastic behaviour at fast loading speeds due to intrinsic muscle properties (force-length, force-velocity, activation dynamics) and loading of serial elements. (5) During passive peak, elastic leg operation was superimposed by distal mass deceleration.